A systematic review of the rates of depression in autistic children and adolescents without intellectual disability. (3rd October 2021) - Stewart, Tracy M.; Martin, Katherine; Fazi, Michela; Oldridge, Jessica; Piper, Allan; Rhodes, Sinead M.
Abstract : Objectives: Increasing evidence suggests that major depressive disorder (MDD) is highly prevalent in autism spectrum disorder (ASD). The current study is a systematic review of rates of depression in autistic children and adolescents, without intellectual disability. Design: Adhering to PRISMA guidelines, a total of 14, 557 studies were identified through five databases (MEDLINE, EMBASE, Cinahl, ERIC, PsycINFO, and Web of Science). Methods: Articles were screened for inclusion and exclusion criteria and 10% double coded at each stage. Nineteen studies met criteria and were retained in the review. Result: The reported rates of depression in autistic children and adolescents varied from 0% to 83.3%. We discuss these findings in relation to method of report (self/informant, interview/questionnaire), recruitment status (clinical/community recruited), and age (pre‐pubertal/adolescent). Conclusion: Rates of depression vary considerably across studies and do not show a particular pattern in relation to methodology, or age. Our research joins a crucial call to action from the research community for future research to improve the identification of depression in autism, which in turn will aid our understanding of the potentially different characterization and manifestation of depression in autism, to ultimately improve assessment and treatment of depression in autistic children and adolescents. Practitioner points: Rates of depression in autistic children and adolescents vary and do not show a particular pattern in relation to methodology or age. Our research joins the call to action from the research community for future research to improve the identification of depression in autistic children and adolescents, which in turn will aid understanding of depression in autism, and ultimately improve assessment and treatment of depression in autistic children and young people. The development of new measures of depression, specifically designed with, and for, children and adolescents with autism, is warranted.